2021
DOI: 10.30918/aerj.91.20.223
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of Covid-19 pandemic on the drawings of pre-school children: A phenomenological study

Abstract: The aim of this study is to investigate how pre-school children perceive the covid-19 pandemic through their drawings. Therefore, 58 children from the age groups 3, 4 and 5 were asked to draw a corona virus-themed picture and then individual interviews which were recorded were conducted with 30 children including 10 from each age group. In the study, while the content analysis was used for the analysis of the data from the pictures, descriptive analysis was used for the interviews. According to the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(4 reference statements)
0
5
0
1
Order By: Relevance
“…Face masks disrupt holistic processing and face perception in children aged 6–14 [ 23 ]. Duran [ 24 ] investigated Turkish preschool children’s perception of the COVID-19 pandemic through their drawings and individual interviews. The children knew what the 2019 Coronavirus was, how it infected people, and how they could protect themselves from the virus with measures such as wearing masks or washing their hands with soap.…”
Section: Introductionmentioning
confidence: 99%
“…Face masks disrupt holistic processing and face perception in children aged 6–14 [ 23 ]. Duran [ 24 ] investigated Turkish preschool children’s perception of the COVID-19 pandemic through their drawings and individual interviews. The children knew what the 2019 Coronavirus was, how it infected people, and how they could protect themselves from the virus with measures such as wearing masks or washing their hands with soap.…”
Section: Introductionmentioning
confidence: 99%
“…Arslan et al, (2021) pointed out in a study carried out with parents of children in preschool that children washed their hands more compared to pre-pandemic periods. In another study carried out by Duran (2021a) with 58 preschool children at the ages of 3-5, it was found that children paid attention to such issues as healthy nutrition and hand washing in order to protect themselves from viruses.…”
Section: Discussionmentioning
confidence: 99%
“…( 2021 ), Raw et al. ( 2021 ) und zum anderen auch mit den Schlussfolgerungen aus erst vor Kurzem publizierten qualitativen Interviews mit Vorschulkindern (Duran 2021 ; Gramigna und Poletti 2020 ). Ferner bestätigen sie auch die Ergebnisse von Steinmayr et al.…”
Section: Diskussionunclassified